Financial Inclusion and Energy Poverty Nexus: Evidence from Pakistan (Journal of Asian Development Studies, 2024)
This study aims to look at the connection between financial inclusion and energy poverty in Pakistan. The data in the time series covers the years 1990–2022. We used two econometric techniques to look at the relationship between the variables: unit root testing and the ARDL model. The findings demonstrate that financial inclusion reduces Pakistan's energy poverty. The study's answers agree on a few policy recommendations that might be used in upcoming policymaking. The results show that financial institution expansion, depth, accessibility, and overall effectiveness significantly impact economic growth in both the full sample and subsamples. We also find that trade openness, labour, capital, and energy consumption substantially impact economic growth in these sections. Moreover, older, or lower-income nations benefit more from financial inclusion in terms of economic production.